Bend into Shape: Techniques for Bioenergetic Therapists - Schroeter, Vincentia; Thomson, Barbara (Psychosozial-Verlag, 2018)
Bend into Shape is the only complete compilation of both classic and modern Bioenergetic techniques. Bioenergetics is a form of somatic psychotherapy created by Alexander Lowen in 1957 and practiced world-wide. The book covers interventions based on body segments, character type, emotions, and various populations such as couples, children and the elderly. The book considers up to date modern issues such as the relational model, including ways to work with transference and countertransference in psychotherapy. It is designed for students of somatic psychotherapy as well as certified Bioenergetic therapists. The authors are both long-time Bioenergetic therapists and experienced trainers in the field.